The Balance of Trade in Southwestern Asia in the Mid-Third Millennium B.C. - Kohl, Philip L. (1978)
comments by L. R. Bäck, H. J. M. Claessen, A. Gilman, ?. L. Hamlin, ?. Hayashi, ?. ?. Lamberg-Karlovsky, H. J. Nissen, J. Oates, A. Ono, D. Potts, H. D. Sankalla, J. G. Shaffer, W. G. Solheim II, M. V. Stark, T. Watkins.